Spaceliner. - Baliç, Ìlkay; Tabur, Ìpek (Ìstanbul : ARTER, 2015)
Anders, Peter ; Boeschenstein, Sandra ; Culbert, Pip ; Eviner, Ìnci ; Grzymala, Monika ; Hess, Nic ; Ìlkin, Gözde ; Kramer, Harry ; Kraneis, Pauline ; Kuhn, Hans Peter ; Leutenegger, Zilla ; Linz, Pia ; Löhr, Christiane ; Mohr, Ulrike ; Oh, Jong ; Schöllhammer, Nadja ; Weber, Heike
Getting to the Point about Lines - Barbara Heinricht ; Pedestrian Spaces, 1913-1975: Notes on a History of Drawing in Space - Michael Glasmeier ; An Encounter in the Third Dimension - Ilkay Baliç
Arter. Istanbul. 15/05/2015 - 2/08/2015
boek